(untitled) (Iraqi Journal of Medical Sciences, 2022)
Background: Genomic studies of hepatitis B virus (HBV) diversity are becoming increasingly significant to understand how HBV mutations interact with a wide spectrum of clinical and pathological disorders. Objective: This study focused on identifying HBV genotypes and determining the status of pre-core (PC) and core promoter (CP) mutants. Methods: Nested polymerase chain reaction was used to identify the viral genotypes of 100 patients with chronic HBV infection. Only 30 samples out of 100 were selected to determine the prevalence of mutations in the PC and CP by Sanger sequencing. Results: Over 95% of the samples had only D genotype and mixed genotypes 5% (B+C+D) in chronic hepatitis B (CHB) patients. G1898A, G1901A, G1910A and G1915A mutations in PC gene were found in total 15 out of 30 (50%) samples, which were distributed in the following proportions: 12 out of 25 (48%) in patients with hepatitis B e antigen (HBeAg) -ve, 8 samples with mutants at G1898A, G1901A, G1910A and G1915A (four mutations), 4 samples with mutants at G1898A, G 1901A and G1910A (three mutations). In addition, 3 out of 5 (60%) in patients with HBeAg +ve, while no type of any mutation was detected in the core gene in patients with chronic hepatitis type B. Conclusion: The genotype D was predominantly prevalent among HBV in CHB patients with 95% and with 5% in mixed genotypes (B+C+D), while genotype B and C were relatively less prevalent among CHB patients than genotype D. The mutations were found in the PC gene at nucleotides G1898A, G1901A, G1910A and G1915A, while no type of mutation was detected in the core gene. Keywords: Genotypes, pre-core mutation, core mutation, HBV Citation: Hussain HT, Al-Shuwaikh AM, Ahmed AM. Hepatitis B virus genotypes and pre-core and core genes mutations in a sample of Iraqi patients with chronic hepatitis B Infection. Iraqi JMS. 2022; 20(2): 217-225. doi: 10.22578/IJMS.20.2.8